SOSIALISASI TENTANG SPESIALISASI KEMAMPUAN ATLET DALAM OLAHRAGA BOLA VOLI - Sujarwo, (TAAWUN, 2021)
This community service aims to provide junior volleyball athletes with an understanding of the role of each player in the team with specialization in individual abilities. The community services method uses a three-way discussion, namely from community services with coaches and athletes using the zoom application media. Pre and post tests were conducted to measure the knowledge of junior athletes about athletes' knowledge of specialization in volleyball. The dedication subjects were 17 junior volleyball athletes in Bantul district. The results of the dedication obtained by the level of knowledge of junior volleyball athletes in Bantul Regency with differences in the mean results 85.88 and after the dedication was carried out 87.64. The more you know the role of each player in the team, the easier it will be for the team to carry out its duties.